Islanding detection in distributed generation system using intrinsic time decomposition. Issue 5 (28th February 2019) - Nale, Ruchita; Venkatanagaraju, Kasimala; Biswal, Sandeep; Biswal, Monalisa; Kishor, Nand
Abstract : This study introduces the implementation of intrinsic time decomposition (ITD) based passive islanding detection technique for distributed generation (DG) system. The proposed method utilises voltage signals and decomposes it into a baseline signal and residual signal. The performance index in terms of energy computed from baseline signal is defined to discriminate between islanding and non‐islanding events. The proposed ITD based technique for islanding detection has been analysed on different types of DGs connected to the system. The performance of the proposed technique is validated via simulation of distribution system modelled in EMTDC/PSCAD. The different critical operating conditions: lower end active and reactive power mismatch and events like capacitor switching, load switching, inception of fault, have been simulated to test the performance of the proposed scheme. The obtained results suggest that the proposed technique exhibits high reliability and has quick response time to detect islanding situation as compared to other passive islanding detection methods.